Analysis of Financial Reporting Fraud with Fraud Hexagon Theory in Financial Companies in the Banking Sub-Sector in 2020-2022 - Dwi Fitriyanto; Triyono (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
In a situation of economic constraints, the risk of fraudulent financial reporting becomes a major concern. This study examines the Fraud Hexagon Theory in identifying fraudulent financial reporting. This study uses a quantitative approach with a focus on financial companies in the banking subsector listed on the Indonesia Stock Exchange (IDX) in 2020–2022, with a total of 47 companies. The sample was selected using purposive sampling, including companies that published complete annual reports and were identified as committing fraudulent financial reporting at least once in three years of observation. The results of the study indicate that financial stability and rationalization have a positive effect on fraudulent financial reporting, while ineffective monitoring, capability, arrogance, and collusion have a negative effect. These findings indicate that financial pressure and internal justification increase the risk of fraud, while the effectiveness of supervision and certain individual factors can reduce the tendency to manipulate financial reporting. This study provides insights for regulators, auditors, and stakeholders in improving supervision and mitigating fraud risks in the banking sector. The resulting policy implications can be used to strengthen the internal control system and reduce the potential for fraudulent financial reporting in the future.